Corrigendum to: Mislabelling may explain why some prohibited invasive aquatic plants are still being sold in Belgium - Van den Neucker Tom; Scheers Kevin (Knowledge and Management of Aquatic Ecosystems, 2023)
Six taxonomic errors and one relevant taxonomic change were discovered after publication of “Mislabelling may explain why some prohibited invasive aquatic plants are still being sold in Belgium” Van den Neucker T, Scheers K. 2022. Knowl Manag Aquat Ecosyst 423: 8. This corrigendum lists the changes that need to be made in the paper and in Appendices A and B. The authors state that this does not change the scientific conclusions of the paper in any way. Corrected versions of Appendices A and B are made available as supplementary material.